TUC National Education Centre - mural, 1986 (London, 1986)
1986 1980-95 "TUC National Education Centre - mural, 1986" [BW0124], 1986, Trades Union Congress The TUC National Education Centre opened in August 1984 in a building formerly used as the Hornsey Art College. It is a residential college offering a programme of courses for union officers and representatives, consultancy services and conference facilities.